2011
DOI: 10.2174/157488511798109592
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Duloxetine in Patients with Chronic Pain Conditions

Abstract: The primary objective of this study is to review the efficacy of duloxetine in treating chronic pain using the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT) recommendations for clinical significance across chronic pain states. These include pain intensity, patient ratings of overall improvement, physical functioning, and mental functioning. This review comprised the side-by-side analyses of 12 double-blind, placebo-controlled trials of duloxetine in patients with chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…Subsequent research has supported this concept. The degree of improvement observed following MCT appears higher than that observed using duloxetine in FM [22]. Prior studies employing synthetic cannabinoids have shown that tolerability of FM patients to nabilone is low [23].…”
Section: Pgicmentioning
confidence: 79%
“…Subsequent research has supported this concept. The degree of improvement observed following MCT appears higher than that observed using duloxetine in FM [22]. Prior studies employing synthetic cannabinoids have shown that tolerability of FM patients to nabilone is low [23].…”
Section: Pgicmentioning
confidence: 79%
“…The results of a recent clinical investigation by Skljarevski et al [67] extended the pain-reducing efficacy of duloxetine in FMS to other disease states characterized by chronic pain, including, diabetic peripheral neuropathy, osteoarthritis and back pain. The results of this study also implied a common mechanism for the action of duloxetine in the reduction of pain intensity as well as for improving physical functioning.…”
Section: Results Of Individual Ms Clinical Trials With Snrismentioning
confidence: 99%
“…[71] Sonrasında ise duloksetin sadece eşlik eden depresyonda değil, aynı zamanda kronik ağrı ve fibromiyalji gibi durumlarda ruhsat alarak bu hastalıkların tedavisinde yaygın kullanılmaya başlanmıştır. [72] Antidepresanlar dışında diğer psikotroplarda romatolojik hastalıklara eşlik eden depresyonda etkili bulunmuştur. İkinci nesil antipsikotikler antidepresan etkinliklerinin de olması ile üzerinde durulan ajanlardır.…”
Section: Romatolojik Hastalıklarda Depresyon Tedavisiunclassified